2017
DOI: 10.4103/jips.jips_5_17
|View full text |Cite
|
Sign up to set email alerts
|

Infection control knowledge and practice: A cross-sectional survey on dental laboratories in dental institutes of North India

Abstract: Aim and Objectives:The aim of the study was to assess the knowledge of dental laboratory technicians regarding infection control and modes of infection control employed by them.Settings and Design:A self-assessment questionnaire-based survey was carried out among dental technicians to assess the knowledge and practice of infection control in dental laboratories.Materials and Methods:Survey instrument containing 16 questions were randomly distributed to 70 dental colleges of North India regarding knowledge of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 7 publications
0
17
2
6
Order By: Relevance
“…More recent findings indicate insufficient knowledge and very limited awareness by dental healthcare personnel (DHCP) in relation to infection control, taking into account the insufficient use of PPEs, low use of sterilized impression tray (13%), rinsing the impressions with water (37.2%) or brushing away debris (2,6%) before disinfection, blood-contaminated impression (25%), improper disinfection of impression (about 40%) or of metallic impression trays, denture prosthesis, bite registration and wax, face bole and fork, and lack of communication (24,7%) with DL about impression disinfection in dental offices [2, 11–13, 39, 4246].…”
Section: Resultsmentioning
confidence: 99%
“…More recent findings indicate insufficient knowledge and very limited awareness by dental healthcare personnel (DHCP) in relation to infection control, taking into account the insufficient use of PPEs, low use of sterilized impression tray (13%), rinsing the impressions with water (37.2%) or brushing away debris (2,6%) before disinfection, blood-contaminated impression (25%), improper disinfection of impression (about 40%) or of metallic impression trays, denture prosthesis, bite registration and wax, face bole and fork, and lack of communication (24,7%) with DL about impression disinfection in dental offices [2, 11–13, 39, 4246].…”
Section: Resultsmentioning
confidence: 99%
“…Because of apprehension and distress about the infection control, disinfecting the impressions has become a cardinal issue in clinical practice. [8]…”
Section: Discussionmentioning
confidence: 99%
“…Although, the students of dental technology who become dental technicians in future, should be educated in this field as well (20). Gupta et al reported that most of the technicians were not aware of basic infection control protocols (21). According to Moradi Khanghahi et al systematic review, the knowledge, attitudes and practice of infection control in Iranian dental settings were found to be inadequate.…”
Section: Discussionmentioning
confidence: 99%